Aktualisasi Manajemen Peningkatan Mutu Berbasis Madrasah - Izza, Ismatul (LP3M Universitas Islam Zainul Hasan Genggong, 2018)
Along with the changing era toward progress, in the era of increasingly free competition like today, educational institutions are required to be able to provide quality education because of poor quality educational institutions over time will be abandoned by society and eliminated by itself The form of efforts to improve the quality of education undertaken by the government is to establish a policy of quality management based on madrasah by delegating authority from the center to the school (madrasah), where the madrasah are given the flexibility and authority to organize and implement up to evaluate the education carried out Title of actualization of quality improvement management based on madrasah. While the formulation of the problem is how the actualization of quality improvement management based on madrasah, what are the supporting and inhibiting factors in actualizing the management of quality improvement based on madrasah. Based on the formulation of the problem, the purpose of this study is to describe the actualization of quality improvement management based on madrasah, and to describe what are the supporting and inhibiting factors in actualizing the management of quality improvement based on madrasah. In data collection methods through observation, interview and documentation, with informants. While to analyze the data using qualitative descriptive technical analysis, that is to describe and interpret the data that have been obtained so that will describe the actual reality in accordance with the existing phenomenonThe result of the research shows that the actualization of management of quality improvement of education can be implemented well, because madrasah is basically the existence of madrasah from, by and for society and it is time for madrasah based quality management is applied in madrasah to improve education quality Actualization of madrasah based quality improvement management as a national policy, firstly do program planning and situation analysis to know the target to be achieved and do SWOT analyst to know how far the readiness of madrasah in order to improve the quality of education After MPMBM planning is completed by giving birth to the program that must be implemented, the head of the madrasah performs the division of workload by providing a proportional portion to each individual or group. In evaluating the head of the madrasah perform regular evaluations every week and any problems From this it can be understood that the supporting factor in actualizing the management of quality improvement based on Madrasah Madrasah is the compactness and high morale spirit of the existing elements ranging from head of madrasah to employees, and completeness of existing infrastructure. Keywords: Quality Improvement Management, Madrasah Based Quality of Education